F. R. Palmer (ed.), Grammar and meaning. Essays in Honour of Sir John Lyons. Cambridge University Press, Cambridge, 1995; xiii + 265 pp. - Fernández Ruiz, Graciela (El Colegio de México, 1997)
Se reseñó el libro: Grammar and meaning. Essays in Honour of Sir John Lyons.